Differentiated Learning Strategies for Students with Learning Difficulties in Regular Elementary Schools - Ameliya, Nurlaila Zulfa; Nur’Aliya, Naila; Renata Elsinta; Kusmana, Suherli (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2026)
The diversity of learning styles among students in regular elementary school classrooms encourages teachers to use flexible teaching methods, especially for students with learning difficulties. This study aims to understand teachers' perspectives, the problems they face, and how they implement different learning approaches for students with learning difficulties in public elementary schools. This research uses a descriptive qualitative approach with a multiple case study design. The research was conducted in three public elementary schools and involved four classroom teachers selected based on their experience in teaching students with learning difficulties. Data were collected through semi-structured in-depth interviews and then analyzed using cross-case and intra-case thematic analysis. The findings show that teachers view students with learning difficulties as individuals who require more guidance and repetition of material, especially in basic reading and writing skills. Learning difficulties are not only considered an intellectual limitation but are also influenced by the environment and support from the family. Some of the main challenges in implementing differentiated learning include limited learning time, large class sizes, and low parental participation. To overcome this, teachers differentiate in terms of content, methods, and learning outcomes by simplifying material, using varied media and methods, providing individual or small group support, and adjusting tasks and expectations. This study emphasizes that differentiated learning is implemented in a flexible and context-appropriate manner and plays an important role in supporting inclusive learning in public elementary.